DECOMPOSITION OF WHITE OAT PHENOTYPIC VARIABILITY BY ENVIRONMENTAL COVARIATES - Loro, Murilo Vieira; Carvalho, Ivan Ricardo; Silva, José Antonio Gonzalez da; Sfalcin, Inaê Carolina; Pradebon, Leonardo Cesar (REVISTA DE AGRICULTURA, 2022)
The study aims to quantify the effects of environmental variables on the interaction between genotypes x environments and to evaluate the sensitivity of white oat genotypes to grain yield in 10 years of cultivation. The experiment took place in the municipality of Augusto Pestana – RS. The experimental design used was in randomized blocks, being evaluated the grain yield of 26 white oat genotypes in 20 complex environments. Greater phenotypic stability was observed for the URS 21 genotype, by the AMMI and GGE methodologies. The URS Corona genotype showed general adaptation, high genetic value and predictable environmental variations by the GGE method and reaction norm. Higher minimum air temperature and lower medium temperature and relative air humidity enhance the productive performance of white oat genotypes. The genotypes URS 22, Fapa Slava, IPR Afrodite and Estampa express positive responses to the covariates temperature medium, maximum, minimum and relative air humidity, respectively. Relative humidity explains more than 50% of the biological variation of white oat genotypes.